Validity Comparison between Moyers and Sitepu Methods in the Javanese Children of 11-14 Years Old - Kaswindiarti, Septriyani; Widayati, Anis Nur (Universitas Muhammadiyah Surakarta, 2021)
Aim: This study aims to compare the validity between Moyers and Sitepu methods in the Javanese children of 11-14 years old. Method: 50 children of 11-14 years old in SMP Al Islam 1 Surakarta that suitable to the study sampling criteria, upper and lower jaw were molded. The result of jaw molds as a study model was used as research samples for direct measurement using Moyers and Sitepu methods with a sliding caliper. The three results were recorded and analyzed using the statistic test of Kruskal-Wallis and post hoc Mann Whitney. Study result: There is no difference in direct measurement result with Moyers method on the lower jaw (p>0.05) and there is a difference in direct measurement result with Moyers method on the upper jaw (p<0,05). Conclusion: Sitepu method is valid for the upper and lower jaw and the Moyers method is valid for the lower jaw of Javanese children of 11-14 years old.